EMPOWERED TO LEAD: ELEVATING BSC NURSING PRACTICE THROUGH LEADERSHIP SKILLS - Musaib Gul (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
Nursing, being a crucial component of healthcare, necessitates skilled individuals who are prepared not only with clinical expertise but also with effective leadership abilities. We investigate the critical function of leadership qualities in the practise of Bachelor of Science in Nursing (BSc Nursing) students in this research. We emphasise the need of integrating leadership education and development into BSc Nursing programmes by analysing the influence of leadership on patient outcomes, team dynamics, and overall healthcare delivery. Furthermore, we address various leadership theories pertinent to nursing practise and recommend techniques for developing future nursing professionals' leadership qualities.